1977
DOI: 10.1093/bja/49.10.1047
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Drugs Given Before Anaesthesia Xxvi: Lorazepam

Abstract: Lorazepam has been studied as preanaesthetic medication given by mouth, i.m. and i.v. Sediation and side-effects and the incidence of anterograde amnesia in patients having a standard operation under methohexitone-nitrous oxide-oxygen anaesthesia were assessed. In a preliminary study of three i.m. (2-, 4- and 8-mg) and six oral (1-,2-,2.5-,4-,5- and 8-mg) doses, the optimum dose was found to be 4 mg for patients with an average weight of 60 kg. This dose was studied in detail when given by all three routes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1979
1979
1998
1998

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Lorazepam doses that produce anxiolysis, amnesis, and sedation were not e¤ective in preventing ketamine psychosis. However, the anesthesia literature suggests that the IV administration of lorazepam at a higher dose than employed in the current study, 4 mg, reduces ketamine psychosis (Dundee et al 1977). At this lorazepam dose, sedative e¤ects interfere with prospective behavioral assessments and amnestic e¤ects could interfere with retrospective self-reports.…”
Section: Lorazepam and Ketamine-induced Psychosismentioning
confidence: 72%
“…Lorazepam doses that produce anxiolysis, amnesis, and sedation were not e¤ective in preventing ketamine psychosis. However, the anesthesia literature suggests that the IV administration of lorazepam at a higher dose than employed in the current study, 4 mg, reduces ketamine psychosis (Dundee et al 1977). At this lorazepam dose, sedative e¤ects interfere with prospective behavioral assessments and amnestic e¤ects could interfere with retrospective self-reports.…”
Section: Lorazepam and Ketamine-induced Psychosismentioning
confidence: 72%
“…Lorazepam has a slower onset and longer duration of action than midazolam. 96 It is the high affinity of lorazepam for cellular receptors that produces its intermediate to long duration of action. Because lorazepam does not require hepatic metabolism and does not yield active hepatic metabolites, it may be a better benzodiazepine choice for the patient with liver disease.…”
Section: Lorazepammentioning
confidence: 99%
“…The frequency of vomiting after anaesthesia in the trimeprazine group was similar to that reported after trimeprazine in previous studies. The frequency of postoperative vomiting after premedication with lorazepam was 39.3%, which is greater than the 10.4% (Dodson and Eastley, 1978) and 15% (Dundee et al, 1977) frequency observed in adults. Both groups received equal amounts of analgesic, following surgery, but whereas trimeprazine has a well recognized antiemetic effect, opinion is divided concerning lorazepam, with both antiemetic and emetic properties reported (Dodson et al, 1976).…”
Section: Discussionmentioning
confidence: 59%
“…The frequency of anterograde amnesia for the venepuncture was less than the 28% rate reported in adults (Dundee et al, 1977). However, amnesia following oral lorazepam is greater for nonemotional or visual events than for painful stimuli (McKay, Dundee and George, 1978;Studd and Eltringham, 1980).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation